An Overview of the Female Reproductive System: A Narrative Literature Review - Andina, Indri (Phlox Institute: Indonesian Medical Research Organization, 2023)
The female reproductive system is a biological system that is responsible for producing, transporting, and storing eggs and facilitating the meeting between eggs and sperm for fertilization. The female reproductive system consists of internal and external organs. This literature review aimed to describe the female reproductive system. Internal organs include the ovaries (ovaries), fallopian tubes (oviducts), uterus (womb), cervix (cervix), and vagina. The ovary is the main female reproductive organ. The two main functions of the ovaries are the secretion of female sex hormones and the development and release of female gametes, or ova. The almond-shaped ovaries are located on either side of the uterus and are supported and supported by the halves mesovarium of the broad, ovarian, and suspensory ligaments. The female reproductive system is also influenced by reproductive hormones such as estrogen, progesterone, and gonadotropins which are produced by the pituitary gland and ovaries.